IMPLEMENTATION OF PROMOTIVE AND PREVENTIVE MANAGEMENT FUNCTIONS FOR ACUTE RESPIRATORY INFECTIONS IN TODDLER - Azriful Azriful; Yudi Adnan; Rahmawaty Rahmawaty (Homes Journal = Hospital Management Studies Journal, 2021)
Background: Acute Respiratory Infectious Disease (ARI) is an acute infectious disease that affects one or more parts of the airway. Objective: This study aims to obtain information related to the implementation of promotive and preventivemanagement functions foracute respiratory infections  in Toddler.Method:The method used is qualitative with a case study approach. The informants consisted of the head of the Puskesmas, officers of the ARIand surveillance programs, health promotion efforts officers, environmental health effort officers, heads of administration, and several mothers of children under five who had suffered from ARI. Result: The results showed that the management function of the promotive and preventive ARI program was still part of the P2PL program in general. This is evidenced by the absence of a special plan made by the Puskesmas regarding the promotional efforts to prevent ARI so that management functions such as planning, organizing, mobilizing, monitoring, funding, and evaluating have not been able to minimize the number of ARI sufferers in children under five. Conclusion: The extension program in the community is still not evenly distributed around the work area of Puskesmas X. The head of the Puskesmas should make policies related to special planning and Standard Operating Procedures (SOP) related to the prevention and control of ARI in children under five.